2010
DOI: 10.1242/jeb.043109
|View full text |Cite
|
Sign up to set email alerts
|

An entomopathogenic Caenorhabditis briggsae

Abstract: SUMMARY Caenorhabditis elegans is a premier model organism upon which considerable knowledge of basic cell and developmental biology has been built. Yet, as is true for many traditional model systems, we have limited knowledge of the ecological context in which these systems evolved, severely limiting our understanding of gene function. A better grasp of the ecology of model systems would help us immensely in understanding the functionality of genes and evolution of genomes in an environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…SCBI on the nematode epidermis or in the gut or bacterial proliferation in the prepared plate caused G. mellonella to die. The pathogenicity shown in Abebe et al (Abebe et al, 2010) is simply the effect of C. briggsae inadvertently introducing Serratia sp. SCBI into and/or onto G. mellonella.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…SCBI on the nematode epidermis or in the gut or bacterial proliferation in the prepared plate caused G. mellonella to die. The pathogenicity shown in Abebe et al (Abebe et al, 2010) is simply the effect of C. briggsae inadvertently introducing Serratia sp. SCBI into and/or onto G. mellonella.…”
mentioning
confidence: 92%
“…Recently, Abebe et al (Abebe et al, 2010) showed that by feeding C. briggsae (and other Caenorhabditis species) Serratia marcescens (Serratia sp. SCBI), they could turn a normally benign nematode into a lethal entomopathogen capable of infecting and killing wax moths (Galleria mellonella).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For transmission between insect hosts, the bacteria colonize the intestine of the nematode's infective juvenile stage [6][7][8] . Recently, several other nematode species have been shown to utilize bacteria to kill insects [9][10][11][12][13] , and investigations have begun examining the interactions between the nematodes and bacteria in these systems 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It is thus overstating the case to say that C. briggsae or any other Caenorhabditis species are actually entomopathogenic nematodes. (Abebe et al, 2010). Their main thesis that "the authors have failed to demonstrate the pathogenicity of Caenorhabditis species and the symbiotic nature of this association" is incorrect.…”
mentioning
confidence: 99%